Legal Protection of Victims of AI-Driven Deepfake Pornography: An Analysis within Indonesian Law - Hidayah, Siti Nur; Hadi Purwanto, Gunawan (Universitas Islam Negeri Alauddin Makassar, 2026)
The development of Artificial Intelligence technology has led to new forms of digital crime, one of which is deepfake pornography. This crime involves the manipulation of a person’s facial identity into pornographic content without consent, resulting in serious violations of privacy, dignity, reputation, and psychological well being. This study aims to analyze the legal construction of deepfake pornography within the Indonesian legal system and to examine the forms of legal protection available for victims. This research employs a normative legal method using statutory and conceptual approaches, supported by prescriptive and interpretative analysis of primary, secondary, and tertiary legal materials. The findings indicate that although several laws, such as the Pornography Law, the Information and Electronic Transactions Law, the Personal Data Protection Law, and the Law on Sexual Violence Crimes, may be applied to prosecute perpetrators, Indonesia still lacks a specific, comprehensive regulation that addresses the unique technical complexities of AI-generated content. This regulatory gap leads to inconsistencies in law enforcement and fails to address the rapid, borderless dissemination of deepfakes, leaving victim protection severely limited, particularly regarding long-term psychological recovery and the complex restoration of digital reputation. This study highlights the urgency of establishing a comprehensive, victim-centered legal framework that integrates criminal, civil, and administrative approaches within a global context, acknowledging that technologically driven harms constitute a pervasive and transnational challenge faced by legal systems worldwide.